Pattern of Dyslipidemia in Patients with Acute Coronary Syndrome in a Cardiac hospital in Nepal - Laudari, Shankar; Poudel, Kiran; Bhurtyal, Sujal; Upadhyay, Hari Prasad (Journal of National Heart and Lung Society Nepal, 2024)
Background: Dyslipidemia is defined as an abnormal concentration of lipids in the blood and is a critical modifiable risk factor for the development of cardiovascular diseases, including acute coronary syndrome (ACS). The aim of the study was to determine the pattern of dyslipidemia among patients with Acute Coronary Syndrome admitted to a cardiac hospital. Methodology: This is a cross-sectional study including consequent 143 patients admitted to Chitwan Mutu Aspatal with a diagnosis of acute coronary syndrome. The study was conducted from July 2021 to Jan 2024 over a period of 2.5years. The patient’s lipid levels were taken within 24 hours from the onset of Acute Coronary Syndrome.Results: Out of total of 143 patients, dyslipidemia was found in majority of patients with low HDL in 92(64.30%) in our study. 53 (37.1%) were females and 90 (62.9%) were males. The mean age of the patients was 62.3013.03 SD (in years). Patients with STEMI had maximum elevation of LDL (52.9%) compared with those having NSTEMI in 44.4% and 31% in Unstable angina patients. Also, low HDL level was detected in the majority of the patients across all spectrum of ACS patients which was statistically significant (p